Hipertensi pada Anak di RS dr. Sardjito Yogyakarta - A.K. Pungky, M.P. Damenik (Berita Kedokteran Masyarakat (BKM), 2006)
Background: The prevalence of hypertension cases in children which were categorized into primary and secondary hypertension was 1-3%. The most common and severe cases were caused by renal diseases. Symptomatic examinations were performed to identity the factors related to hypertension.Objective: To know the clinical appearance of hypertension in children, the infection, and its complications. Patelnts &Methods: A retrospective analysis on children with hypertension hospitalized at Dr. Sardjito Hospital from 1996-2005 was conducted. The criteria of hypertension were based on 'The Second Task Force on Blood Pressure Control in Children" curve (1987) which were the average systolic and diastolic blood pressure 95 percentile by age and sex at 3 successive measurements.Results: hypertension was found in 146 (1,28%) of 1.169 hospitalized children. Of all children with hypertension 63% were male and 37% were female. The underlying diseases of hypertension included acute glomerulonephritis (GNA) (71%), steroid treated nephrotic syndrome (21%), and others (8%). Children with severe hypertension (70%), moderate hypertension (22%), and mild hypertension (8%).Conclusion: Due to high number of children with severe hypertension in this study and the major cause was GNA, early management using antibiotics in patient with GNA in order to prevent worse condition was needed. Keywords: hypertension, acute glomerulonephritis, nephrotic syndrome, corsticosteroid